SWOT Analysis in Enhancing School Competitiveness in the Era of Globalization: A Strategic Approach Based on Educational Management - Chelsi Hestivik; Yosi Fadila; Srikandi Yudistira; Muhammad Syaifuddin (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2026)
This study aims to analyze the utilization of SWOT analysis in enhancing school competitiveness in the era of globalization. The research employs a qualitative descriptive approach with a library research design by systematically reviewing relevant scientific sources, including national and international journal articles, academic books, and educational policy documents. The findings indicate that SWOT analysis plays a strategic role in identifying internal factors (strengths and weaknesses) as well as external factors (opportunities and threats) that influence the performance and competitiveness of educational institutions. The implementation of SWOT functions not only as a planning tool but also as an adaptive managerial framework that responds to policy changes, technological advancements, and global demands. Strategies derived from the SWOT matrix (SO, WO, ST, WT) contribute to improving learning quality, strengthening human resource capacity, optimizing the use of digital technology, and enhancing institutional reputation within the community. However, this study also reveals that the application of SWOT remains largely conceptual and has not been fully contextualized at the school level. Therefore, a more operational, integrative, and data-driven approach is required for its effective implementation. This research contributes to the field of educational management by providing an applicable conceptual framework based on SWOT analysis